Developing sustainability index for Malaysian palm oil industry with fuzzy analytic network process - Ngan, Sue Lin (Animo Repository, 2018)
Copyright © 2018, AIDIC Servizi S.r.l. As one of the world’s major exporters of crude palm oil, Malaysian palm oil industry plays a crucial role in the country’s economic development. The utilization of palm oil biomass residues into high value-added products also has grown tremendously in recent years and has significantly contributed to the country’s GDP. Despite obvious benefits to the country’s economy and welfare of its population, the oil palm industry also contributes to environmental degradation, both at the input and output sides of its activities. Therefore, it is imperative that the implementation of sustainable supply chain and green logistics practices should be considered within the industry. With increasing pressure from various stakeholders to act and report on sustainability best practices, a number of sustainability assessment tools have emerged and some of which are adopted by industry players to demonstrate their commitment to sustainable development. Sustainability indicators and composite index are increasingly recognized as a powerful tool for policy making and corporate communication in providing information on sustainability performance in areas such as environment, economy and society. The uncertain parameters are particularly noticeable in the palm oil industry since the demand and supply are very volatile, and there are many uncertain variables associated with the industry’s supply chain. The fuzzy analytical network process (FANP), a multi-criteria decision-making analysis tools that has been applied to problems in various industries is adopted in this work. A complex of relationships between economic, environmental and social performance indicators related to the oil palm industry is constructed as a network model. Pairwise judgements are then elicited from experts to derive priority weightages for every component in the sustainability model. Varying with traditional ANP, using fuzzy numbers for pairwise comparisons ratios allows the confidence level of the judgements to be quantified explicitly. Converged priority vector that captures the correlation and importance of named indicators is then converted to form the sustainability index. The sustainability index will provide a framework for best practices assessment for the oil palm industry and is likely to raise the performance and delivery of sustainability. Such a comprehensive index will also stimulate positive change within the industry, through both internal performance and external perception and image branding.